The incidence and origin of segmental aneuploidy in human oocytes and preimplantation embryos - Babariya, D; Fragouli, E; Alfarawati, S; Spath, K; Wells, D (Oxford University Press, 2017)
Study Questions What is the incidence, origin and clinical significance of segmental aneuploidy in human oocytes and preimplantation embryos? Summary Answer Segmental aneuploidy occurs at a considerable frequency in preimplantation embryos with a majority being mitotic in origin. What is Known Already In recent years, accurate techniques for the detection of aneuploidy in single cells have been developed. Research using such methods has confirmed that aneuploidy is a common feature of human oocytes and preimplantation embryos. However, thus far research has mainly focused on loss or gain of whole chromosomes. We utilized sensitive molecular methods to study another important form of cytogenetic abnormality at the earliest stages of human development, namely segmental aneuploidy. Study Design, Size, Duration Chromosomal copy number data was obtained from oocytes and embryos of 635 IVF patients, who requested chromosome screening for various reasons, most commonly for advanced maternal age or previously unsuccessful IVF treatments. A total of 3541 samples comprising of 452 human oocytes, 1762 cleavage stage and 1327 blastocyst stage embryos were investigated in the present study. Participants/Materials, Setting, Methods Whole genome amplification (Sureplex, Illumina) was performed on cells biopsied from oocytes and embryos of IVF patients who requested chromosome screening. The samples were subsequently processed and analyzed for their chromosome complement using microarray comparative genomic hybridization (aCGH), (Illumina, Cambridge, UK). Main Results and the Role of Chance Segmental abnormalities, involving loss or gain of chromosomal fragments in excess of 15 Mb, were found to occur at a high frequency. The incidence of such abnormalities was 10.4% in oocytes, but this increased dramatically during the first 3 days of embryonic development (24.3%), before starting to decline as embryos reached the final (blastocyst) stage of preimplantation development (15.6%). While some segmental errors were clearly of meiotic origin, most appear to arise during the first few mitoses following fertilization. The reduction in frequency at the blastocyst stage suggests that many cells/embryos affected by segmental abnormalities are eliminated (e.g. via arrest of the affected embryos or apoptosis of abnormal cells). Interestingly, sites of chromosome breakage associated with segmental aneuploidy were not entirely random but tended to occur within distinct chromosomal regions. Some of the identified hotspots correspond to known fragile sites while others may be considered novel and may be specific to gametogenesis and/or embryogenesis. Limitations Reasons for Caution The cytogenetic analysis was performed on biopsies of embryos, which might not be representative of the true incidence of mosaic segmental aneuploidy of the entire embryo. Wider Implications of the Findings The findings of this study are valuable for understanding the origin of subchromosomal duplications and deletions, a clinically important class of abnormalities that are a common cause of congenital abnormalities and miscarriage. Furthermore, the results provide additional evidence that control of the cell cycle is more relaxed during the first few mitotic divisions following fertilization, permitting DNA double-strand breaks to occur and persist through cell division. The data are also of great relevance for preimplantation genetic testing, where the detection of segmental aneuploidy is currently considered problematic for embryo diagnosis and patient counseling.